The Potential of Promotional Media as A Marketing Instrument for Open and Distance Higher Education: A Segmentation Study - Budiman, Rahmat; Wiradharma, Gunawan; Harsasi, Meirani; Riana, Kurnia Endah; Riady, Yasir (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
This research identifies market segments among university students based on media promotion usage. It examines the impact of media promotions on the choice of programs and institutions of open and distance university institutions. This study used a quantitative methodology, and the population studied consisted of all currently enrolled Universitas Terbuka students throughout Indonesia, with a total sample of 2,250 people. In this research, market segmentation has been carried out using the cluster method, which includes demographic, geographic, psychographic, and behavioral segments. The demographic segment that is assessed age and gender of students, recent graduates, and income; The geographic segment is mapped to the origin of the UT regional offices; the psychographic segment includes reasons for studying and choosing UT; and the behavioral segment from which information is first and most effective. This research implies that the results can be used as a reference in supporting higher education promotion. The Novelty of this study is that no other studies have compared the potential of promotional media as a marketing instrument for open and distance higher education.